Reconstruction of the Electromagnetic Field in Layered Media Using the Concept of Approximate Transmission Conditions - Ozdemir, Ozgur; Haddar, Houssem; Yaka, Ali (Institute of Electrical and Electronics Engineers (IEEE), 2011)
We propose a fast and stable method to reconstruct the electromagnetic field in layered media from overdetermined data on the outer boundary. This procedure can be used for instance as a data pre-processing in inversion algorithms to accurately image buried objects under known stratified structures. Our method is based on successive use of so-called approximate transmission conditions that provide accurate reconstructions for layers with sufficiently small width. The feasibility and efficiency of the proposed method are demonstrated by numerical experiments.
Keywords: [SPI.ELEC]Engineering Sciences [physics]/Electromagnetism; [SPI.ELEC] Engineering Sciences [physics]/Electromagnetism